Sublethal Heavy Metal Stress Stimulates Innate Immunity in Tomato - Nilanjan Chakraborty; Swarnendu Chandra; Krishnendu Acharya (The Scientific World Journal)
Effect of sublethal heavy metal stress as plant biotic elicitor for triggering innate immunity in tomato plant was investigated. Copper in in vivo condition induced accumulation of defense enzymes like peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL), and β-1,3 glucanase along with higher accumulation of total phenol, antioxidative enzymes (catalase and ascorbate peroxidase), and total chlorophyll content. Furthermore, the treatment also induced nitric oxide (NO) production which was confirmed by realtime visualization of NO burst using a fluorescent probe 4,5-diaminofluorescein diacetate (DAF-2DA) and spectrophotometric analysis. The result suggested that the sublethal dose of heavy metal can induce an array of plant defense responses that lead to the improvement of innate immunity in plants.